2018
DOI: 10.2116/analsci.18p332
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multiply Charged Poly(ethylene oxide-co-propylene oxide) Using Electrospray Ionization-Ion Mobility Spectrometry-Mass Spectrometry

Abstract: Poly(ethylene oxide), poly(propylene oxide), and their copolymer (poly(EO-co-PO)) were analyzed by electrospray ionization-ion mobility spectrometry-mass spectrometry (ESI-IMS-MS). ESI produced multiply charged analytes of 2 to 5 Na + additions, and they were separately observed in a 2D map of m/z value vs. drift time. The collision cross-section of the analyte polymers was almost linearly proportional to (molecular weight) 0.644 , except for the analytes with 2Na + addition; a nonlinear relation called "foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Indeed, IMS-MS has been extensively used for analyzing multiply charged polymers. [20][21][22][23][24][25][26][27] The molecular distribution of polymers represents another problem for mass spectra interpretation, but the use of MS/MS can limit the distribution to be analyzed. In this case, the first MS selects polymers of a certain m/z range, and the selected ions are analyzed in the second MS after CICS, in which ions attached to the polymers are partially reduced by a relatively soft collision without (or with slight) degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, IMS-MS has been extensively used for analyzing multiply charged polymers. [20][21][22][23][24][25][26][27] The molecular distribution of polymers represents another problem for mass spectra interpretation, but the use of MS/MS can limit the distribution to be analyzed. In this case, the first MS selects polymers of a certain m/z range, and the selected ions are analyzed in the second MS after CICS, in which ions attached to the polymers are partially reduced by a relatively soft collision without (or with slight) degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IMS can separate ions of the same m/z value but different z value generated from ESI. Indeed, IMS‐MS has been extensively used for analyzing multiply charged polymers 20–27 . The molecular distribution of polymers represents another problem for mass spectra interpretation, but the use of MS/MS can limit the distribution to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Ito et al went a step further by analyzing larger multiply charged PEO, PPO, and PEO- b -PPO- b -PEO copolymers . They probed the influence of the PEO/PPO composition on the IMS response .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for sufficiently low z / L , all polymer ions adopt a spherical conformation, regardless of their charge. For critical z / L ratios, structural transitions between extended and compact ion shapes are usually witnessed and are evidenced by discontinuities in CCS versus mass evolutions. In the study on multiply charged homo and copolymers led by Ito, the EO/PO content was shown to play a significant effect on the chain length at which the extended/compact structural transition occurs …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Compared with other techniques for characterization of analytes, MS has significant advantages in speed, sensitivity and specificity. [11][12][13][14][15][16] Electrospray ionization (ESI) is one of the soft ionization techniques for MS analysis and ESI-MS has been widely used to characterize protein. 17 Under ESI-MS conditions, a protein molecule is typically detected as multiple-charged ions, and thus charge state distribution (CSD) of protein could be related to protein conformation.…”
Section: Introductionmentioning
confidence: 99%